Analyzing the Key Drivers of Satisfaction and Loyalty Among Food Delivery App Users - Setiawan, Rony; Aprillia, Ariesya (Pandawan, 2025)
This study investigates the factors affecting user satisfaction and loyalty in food delivery apps, particularly focusing on variables such as information quality, pri- vacy and security, and perceived danger of Covid-19. The research adopts a quantitative, causal-explanatory design, with a sample size of 208 respondents. Data were collected using a structured survey, and the analysis was conducted with SPSS Amos and Partial Least Squares Structural Equation Modeling (PLS SEM). The study reveals significant relationships between usage intention, ac- tual usage, and customer satisfaction, with a specific emphasis on the role of promotion in increasing user satisfaction and loyalty. Variables such as ease of use, navigation design, and packaging safety, however, were found to have no significant impact on usage intention or actual usage. This study also high- lights the evolving consumer behavior in the food delivery industry, especially post-pandemic, where safety and convenience remain critical. The findings pro- vide valuable insights for businesses in the digital marketplace, helping them understand the changing dynamics of consumer preferences. By refining ser- vice offerings and focusing on key influencing factors, food delivery companies can enhance their market competitiveness and customer retention strategies.